2020
DOI: 10.1111/acel.13216
|View full text |Cite
|
Sign up to set email alerts
|

Similar burden of pathogenic coding variants in exceptionally long‐lived individuals and individuals without exceptional longevity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
2
7
1
Order By: Relevance
“…In contrast to previous literature that could not identify a significant difference in the overall burden of disease variants in ELLIs [7,25], we showed here that, on average, ELLIs carry a lower burden of variants associated with AD, CAD, and lupus. In addition, we showed that ELLIs have higher PRS for cognitive function.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to previous literature that could not identify a significant difference in the overall burden of disease variants in ELLIs [7,25], we showed here that, on average, ELLIs carry a lower burden of variants associated with AD, CAD, and lupus. In addition, we showed that ELLIs have higher PRS for cognitive function.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, our results agree with the recent discovery of lower polygenic risk for AD in centenarians and their offspring of Ashkenazi Jewish descent [25]. Our findings regarding AD, CAD and cognitive function are consistent with this previous work, as well as the resilience to AD and CAD seen in ELLIs.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also complement those of Timmers et al, [26] finding associations between a lifespan PRS and common diseases in the UKBB. Importantly, our results also agree with the recent discovery of a lower burden of heterozygous variants for AD in centenarians and their offspring of Ashkenazi Jewish descent [27]. Overall, our findings regarding AD, CAD, and cognitive function are consistent with previous work, which considers polygenic risk beyond genome-wide significant variants and is sufficiently powered.…”
Section: Discussionsupporting
confidence: 92%
“…This low prevalence is all the more counterintuitive given that these oldest-old are indistinguishable from the general population by (a) their number of risk alleles for NCD [42], as well as (b) by their lifestyles [43]. This observation has been confirmed in American Ashkenazi Jews, a population whose strong founder effect (loss of genetic variation that may occur when a few individuals from a large population establish a new population that subsequently may present with distinctively different genotypical and phenotypical profiles) suggests larger statistical power in finding gene-longevity associations [44]. The effect of genes on longevity has recently been estimated to be below 10% [45].…”
Section: Observation 2: Healthy Centenarians Are Indistinguishable By Genes and Lifestylementioning
confidence: 81%